2016
DOI: 10.1590/1982-021620161819515
|View full text |Cite
|
Sign up to set email alerts
|

Autopercepção das condições de trabalho por professores de ensino fundamental

Abstract: RESUMO Objetivo: investigar a percepção dos aspectos ambientais e psicossociais do trabalho de professores de escolas públicas de ensino fundamental e relacionar aos sintomas de desconforto vocal. Métodos: estudo transversal com amostra probabilística de professores de escolas municipais. Participaram do estudo 90 indivíduos (18 homens e 72 mulheres) distribuídos nas faixas etárias de 24 a 65 anos. O instrumento de investigação foi um questionário com 40 questões composto por 5 blocos de perguntas. Foram rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
(27 reference statements)
0
9
0
6
Order By: Relevance
“…Although other studies contemplate the relationship of vocal symptoms with the emotional scope of teachers 30 , with the capacity to perform activities at work 11,12 , and with psychosocial and work organizational characteristics 31 , the present study is a pioneer in the field by presenting the association between vocal behavior profile and well-being in teachers. A higher proportion of well-being perception was observed among teachers who reported good vocal behaviors or presented lower risk of vocal problems.…”
Section: Discussionmentioning
confidence: 93%
“…Although other studies contemplate the relationship of vocal symptoms with the emotional scope of teachers 30 , with the capacity to perform activities at work 11,12 , and with psychosocial and work organizational characteristics 31 , the present study is a pioneer in the field by presenting the association between vocal behavior profile and well-being in teachers. A higher proportion of well-being perception was observed among teachers who reported good vocal behaviors or presented lower risk of vocal problems.…”
Section: Discussionmentioning
confidence: 93%
“…It is pointed out as one of the factors that interferes in the concentration inside the classroom, in the academic performance and in the intelligibility of the classes. Studies have confirmed that noise is a contributing factor for the communicative process not occurring effectively, also interfering in the listening skills, making it difficult to transmit and receive information and directly interfering in the teaching-learning process (1)(2)(3)(4)(5)(6)(7)(14)(15)(16)22) .…”
Section: Discussionmentioning
confidence: 99%
“…The noise present in classrooms is a worrisome factor and produces undesirable effects on both professors and students (1)(2)(3)(4)(5)(6)(7)(14)(15)(16)(23)(24)(25) . Since the university is the place to prepare for entry into the labor market, attention must be paid to this factor so that the teaching-learning process is not impaired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations